Vitamin D in patients with Hashimoto's disease: a systematic review and meta-analysis - Josiane Marlei Muller Fernandes dos Santos (São Paulo State University (UNESP), 2021)
One of the most common thyroid dysfunctions is Hashimoto's disease (HD), characterized by the production of specific antibodies against thyroid gland antigens (Anti-Tg and Anti-TPO). Recent studies have suggested that vitamin D supplementation, associated with levothyroxine, may contribute to the control of this autoimmune disease. However, secondary studies on this topic, such as systematic reviews and meta-analyses, are still scarce. Thus, the present study aimed to evaluate the efficacy and safety of vitamin D in patients with HD through a systematic review with meta-analysis. Randomized clinical trials were selected on the Pubmed, Scopus, and Web of Science databases. Studies comparing groups of HD patients supplemented with vitamin D and non-supplemented HD patients were included. The following outcomes were considered: TSH, T3, T4, Anti-Tg, Anti-TPO, and adverse drug reactions. The risk of bias was performed according to the Cochrane recommendations (RoB v. 2.0), and the quality of evidence was evaluated by the GRADE system. A total of 766 studies were identified in the databases, of which 7 met the eligibility criteria. None of the studies indicated the occurrence of adverse reactions with vitamin D supplementation in any administered dosage. Supplemented patients had a significant reduction in serum TSH levels compared to the control group (mean difference = -0.180 (95% CI [-0.316 to -0.045]), p = 0.009), suggesting that thyroid function was more controlled in the intervention group. However, for the other outcomes, no statistically significant differences were observed between the groups. Additionally, most of included articles (n=5/7) had some concerns or high risk of bias, and the quality of evidence revealed a moderate confidence for almost all outcomes; so the results must be interpreted with caution. Thus, more consistent, and robust clinical trials need to be carried out to confirm the efficacy of vitamin D supplementation in patients with HD.